Cytostatic activity of Geranium robertianum L. extracts processed by membrane procedures - Elena Neagu; Gabriela Paun; Daniel Constantin; Gabriel Lucian Radu (Arabian Journal of Chemistry, 2017)
In the present study the antioxidant and cytostatic capacities of some 8% Geranium robertianum (geranium) aqueous extracts processed by membrane procedures (micro- and ultrafiltration) were determined. The extracts were purified by microfiltration and then concentrated by successive ultrafiltrations using Millipore membranes with 10,000 and 1000 Da cut-off. Two methods were used to establish the extracts’ antioxidant activity: DPPH and ABTS; the cytostatic capacity was evaluated on HEp-2p cell lines, by a qualitative method (cytochemical stain with Giemsa solution) and quantitative one (MTT test). Four concentrations of Geranium aqueous extracts were used to test cell viability: 100, 500, 1000 and 2000 μg/mL, 24 and 48 h, against the control culture (100% viability). The concentrated samples had the highest content of total polyphenols and the strongest antioxidant effect, having also the biggest impact upon cell viability.